2022
DOI: 10.1186/s12893-022-01725-6
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative outcomes of minimally invasive adrenalectomy: do body mass index and tumor size matter? A single-center experience

Abstract: Background Since Gagner performed the first laparoscopic adrenalectomy in 1992, laparoscopy has become the gold-standard procedure in the treatment of adrenal surgical diseases. A review of the literature indicates that the rate of intra- and postoperative complications are not negligible. This study aims to describe the single-center experience of adrenalectomies; and explore the associations between body mass index (BMI) and tumor volume in main postoperative outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Studies have shown that the laterality and size of adrenal tumors (for tumors < 6 cm) did not affect the duration of surgery or postoperative morbidity, either for LTA or RPA. Therefore, these two variables were not included as independent variables in our matching [ 37 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that the laterality and size of adrenal tumors (for tumors < 6 cm) did not affect the duration of surgery or postoperative morbidity, either for LTA or RPA. Therefore, these two variables were not included as independent variables in our matching [ 37 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…While LA is the gold standard for managing small adrenal masses, its application for larger lesions (>5 cm) remains controversial due to concerns about technical feasibility, oncological safety, and limited high-quality evidence ( 5 ) Therefore, a systematic review and meta-analysis was carried out to comprehensively assess the existing literature, address knowledge gaps, and inform clinical practice, which ultimately impact patient care by establishing the efficacy and safety of LA for large masses. This study was conducted to evaluate the feasibility of LA in adrenal masses greater than 5 cm in terms of safety, effectiveness, and complications.…”
Section: Introductionmentioning
confidence: 99%